Conductas agresivas de los niños de una comunidad en el CCPP. Campo Alegre - Chincha Baja, 2020 - Quispe Peña, Quispe Peña (2020)
The present work aimed to describe the level of aggressive behaviors in children of a community in the CCPP. Campo Alegre - Chincha Baja, 2020. This research is of a quantitative approach, basic type, descriptive level and with a non-experimental design, the sample was made up of 20 parents, to whom the Aggression Behavioral Check List was applied in Children (Savina Varona, 2018) composed of 18 items. Once the results were analyzed, which went through a statistical process. The results indicate that 5% of the children present a high level, 35% a moderate level and 60% a mild level of aggressive behaviors; Regarding the dimensions, in the physical active aggressive behavior dimension, it was found that 30% of them are at a high level, 55% of them a moderate level and 15% of them are at a mild level. In the dimension, physical passive aggressive behavior, 95% of them. Keywords: Aggressive behaviors, children, aggressiveness. Aggressive behaviors, children, aggressiveness.